Prevalence of hypertension and its associated modifiable risk factors among rural and urban adults of field practice area of Jhalawar Medical College, Jhalawar - Bindal, Hemant Kumar; Singh, Lakhan; Kumar, Vinod; Dubey, Deepak Kumar; Shukla, Uma Shankar; Qurishi, Asif Ahmed (International Journal Of Community Medicine And Public Health, 2022)
Background: The behavioral and biological risk factors, with a predisposition to the development of high blood pressure, are use of tobacco and alcohol, physical inactivity, obesity, increased fat, sodium intake, low fruit and vegetable intake. HT is called a “silent killer”. Majority of people with hypertension are unaware of the problem because it may have no warning signs or symptoms. Objectives were assessment of the prevalence of hypertension and associated modifiable risk factors among adults in the practice area of rural and urban area of Jhalawar Medical College, Jhalawar. Methods: The present observational cross-sectional study was conducted on adults of rural and urban dwellers of field practice area of Jhalawar Medical College, Jhalawar. By stratified random sampling method, 1418 participants were selected and included in our study during the study period that fulfilled our inclusion and exclusion criteria. Results: The overall prevalence of hypertension found was 18.6%. In the present study, the association of hypertension with risk factors like tobacco use, BMI, and waist hip ratio was found to be significant in rural areas. While in urban areas, the prevalence of hypertension was found to be statistically significant with calorie intake, tobacco use, and BMI and waist hip ratio. The risk factor for calorie intake was found to have an insignificant association with rural areas. Conclusions: The present study revealed that around one fifth of adults had hypertension. The prevalence of hypertension was significantly higher in urban areas than in rural areas.